Teaching Vocabulary Using Drink Package For The Fourth Grade Students Of SD Negeri 1 Krebet Masaran Sragen In 2012/2013 Academic Year - Nugraha, Fradha Dhamara Widhi; , Titis Setyabudi, S.S, M.Hum; , Dra. Dwi Haryanti M.Hum (2013)
In this study aimed is teaching vocabulary using drink package. The samples of this study are fourth year of SD Negeri 1 Krebet Masaran Sragen in 2012/2013 academic year. To take the samples, the writer use teacher's role, learner's role, and classroom activity. The writer also give the pre-test and posttest to know how far the students can achieve the target vocabulary using drink package. The writer took one classes for this research, each class consist 40 students. The result of this study that is by using drink package the students can achieve the target vocabulary well. So with drink package is more effective than just using a handbook.